Investigation of factors related to the behavior of reporting clinical errors in nurses working in educational and medical centers in Rasht city, Iran - Somayeh Abry; Fardin Mehrabian; Saeed Omidi; Mahmood Karimy; Parisa Kasmaei; Katayoun Haryalchi (BMC, 2022)
Abstract Background Report of medical error is one of the effective components in the quality of healthcare services. A significant part of medical errors can be prevented by acting appropriately. The theory of planned behavior offers a framework in which the nurse intention to perform the behavior of error reporting is investigated. This study was conducted to determine the factors related to the behavior of reporting clinical errors in nurses working in educational and medical centers in Rasht based on the theory of planned behavior in 2020. Methods In this descriptive-analytical study, 326 nurses in all medical centers in Rasht were selected by the multi-stage random sampling method. Data collection tool was a valid and reliable questionnaire based on the theory of planned behavior. Data analysis was conducted using the SPSS software, analysis of variance, correlation, and linear regression. Results 39% of nurses reported that they had reported a medical error, and the average number of error reports per nurse during the last 3 months was 1.42 errors. The predictive power of the theory of behavioral intention was 47%, and predictive constructs were attitude (B = .43), perceived behavioral control (B = .33), and subjective norm (B = .04) using linear regression. The predictive power of the theory for nurses' behavior was 3.1%. None of the demographic variables played a role in predicting the behavior of nurses' reporting clinical error, and no behavioral intention predicted the behavior of nurses' reporting clinical errors. Conclusion The theory of planned behavior expresses the factors affecting the behavior intention of nurses' reporting clinical errors satisfactorily. However, it was an inappropriate theory in behavior prediction. It appears that factors, such as fear of consequences of error reporting, social pressures by colleagues and officials, and lack of knowledge and skills required to identify medical errors, are the barriers to conversion of intention to the behavior of reporting clinical errors. It is necessary to provide the ground to increase nurses' report of clinical errors by acting appropriately.